Avaliação comportamental não clínica do metileugenol em modelo de depressão induzida por dexametasona com fêmeas - Cavalcante, Ikla Lima (2018)
Considered a serious mood disorder, depression has been pointed out as a disabling condition in many cases. Studies have shown that stress has been important for the onset of this disease and, along with several other environmental conditions and abnormalities, provide such an event. In this way, it is always sought to improve the forms of treatment, in a way that provides better efficiency to the patients affected. In view of this, essential oils have many bioactive compounds, such as phenylpropanoids. These have different pharmacological activities, such as anxiolytic, anti-inflammatory, anticonvulsive and antidepressant. Methyleugenol is a phenylpropanoid, a structural analogue of eugenol, which has already exhibited various pharmacological activities. Thus, the lack of research on the antidepressant activity of methyleugenol encouraged the accomplishment of this work. The present research investigated the potential antidepressant activity of methyleugenol in adult female mice submitted to the dexamethasone-induced stress model. For this, the animals received a pre-administration of dexamethasone (64 μg / kg s.c.) 3h30min, before performing the behavioral tests of tail suspension, splash test and open field. Methyleugenol (25, 50 and 100 mg / kg i.p) and imipramine (10 mg / kg i.p.) were administered 45 minutes and 30 minutes, respectively, prior to testing. In the tail suspension test, for the latency parameter for immobility, methyleugenol at a dose of 50 mg / kg was able to increase latency compared to the dexamethasone group. And for the immobility time, methyleugenol at the dose of 50 and 100 mg / kg decreased the immobility time compatible with the standard drug imipramine. Then the animals were evaluated in the splash test, in the latency parameter for grooming the doses of 25 and 50 mg / kg of methyleugenol and imipramine decreased this latency in relation to dexamethasone. Doses of 25 and 50 mg / kg, and imipramine increased the grooming time when compared to the group of animals that exclusively received dexamethasone. In the open field test, methyleugenol at doses of 25, 50 and 100 mg / kg and imipramine increased the number of crosses; and at the dose of 50 mg / kg increased the percentage of dwell time at the center of the open field when compared to dexamethasone. As for latency for rearing, the 50 mg / kg dose of methyleugenol decreased latency, and no significant differences were found between the groups evaluated for the number of rearing. In the evaluation of the possible mechanisms of action of methyleugenol, the tail suspension test at the dose of 50 mg / kg was used, which presented better effects in the tests described. Administration of the SC23390 antagonist demonstrated the participation of D1 dopaminergic receptors in the anti-depressant activity of methyleugenol, as well as α1-adrenergic receptors with the use of the prazosin antagonist and serotonergic receptor with the use of a serotonin-PCPA synthesis inhibitor. The findings demonstrate that methyleugenol did not interfere in the locomotor activity of the animals and presented a relevant antidepressant activity through dopaminergic D1 and α1-adrenergic receptors.